IMPLEMENTASI MODEL LEARNING CYCLE7E MELALUI PENGGUNAAN PETA KONSEP BERMEDIA KOMPUTER PADA MATA KULIAH GEOMETRI - Ratih Purnamasari; Resyi A. Gani (Pendidikan Dasar - Pascasarjana Universitas Negeri Jakarta, 2018)
ABSTRACT The purpose of this study is to improve the learning outcomes of PGSD students in geometry courses through the implementation of the 7E cycle learning model with the use of computer-generated concept maps. This research was conducted by Classroom Action Research Method (PTK) Kemmis and Taggart model, consisting of planning, acting, observing, and reflecting. Instruments used in the form of tests to create a concept map of the material that has been studied, and non-test in the form of: interviews, observation sheet (checklist), and field notes. The criteria of success in this study is that all students get a minimum value of B. The results of this study indicate that student learning outcomes from one cycle to the next cycle always increased. In cycle 1, the number of students who got A score of 31%. In the second cycle increased to 52%. While the number of B values ​​obtained by students in cycle I to cycle II also increased, from 22% to 26%. Although it continues to increase, in cycle II there are still students who get the value of C, so the research continued on cycle III. In the third cycle there is no more students who get the value of C. From this study can be concluded that the implementation of the 7E cycle learning model through the use of computer-based concept map can improve the cognitive learning outcomes of PGSD students in geometry courses. Keyword: learning cyle 7E, computer media, learning outcomes